Prognostic Role of Systemic Inflammatory Indexes in Germ Cell Tumors Treated With High-Dose Chemotherapy - Cursano, Maria Concetta; Kopf, Barbara; Scarpi, Emanuela; Menna, Cecilia; Casadei, Chiara; Schepisi, Giuseppe; Lolli, Cristian; Altavilla, Amelia; Gallà, Valentina; Santini, Daniele; Tonini, Giuseppe; Chovanec, Michal; et al. (Frontiers in Oncology, 2020)
High-dose chemotherapy (HDCT) has curative potential in relapsed/refractory germ cell tumors (GCT). Due to the complexity of this population and the toxicity of HDCT, we evaluated the association between blood-based systemic inflammatory indexes and the outcome of GCT patients undergoing salvage treatment with HDCT in order to define additional prognostic factors able to orient clinical decision. Baseline characteristics, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and the systemic immune-inflammation index (SII) of 62 patients undergoing HDCT for GCT were retrospectively collected. The aim is to evaluate the correlation between each inflammatory marker (NLR, PLR, and SII) and response to HDCT, overall survival (OS), and progression-free survival (PFS). Using the receiver operating curve to identify the best cutoff values, it was found that patients with GCT with NLR ≥3.3 and SII ≥844,000 had shorter PFS and inferior OS. In the multivariable analysis including inflammatory markers, the International Prognostic Factor Study Group (IPFSG) risk group, age, and previous line of treatment, NLR ≥3.3 and SII ≥844,000 were identified to be independently associated with shorter PFS and OS. Moreover, NLR, PLR, and SII significantly correlate with overall response to HDCT. Associating IPFSG prognostic score to inflammatory markers at baseline of HDCT may improve prognostic information and could help physicians to make more personalized treatment decisions.